Do mothers treat children who are similar to them better? The relation between maternal–adolescent neuroticism congruence and a punitive parenting style - Peng, Shun; Xu, Lei; Chen, Jiwen; Cai, Shuangshuang (Frontiers in Psychology, 2022)
Parenting style refers to the relatively stable behaviors parents display during the childrearing process. It is an important factor in children’s socialization and the mother-child relationship. Drawing upon theoretical and empirical studies on maternal personality, adolescent personality, and parenting style, our study tested the relationship between maternal-adolescent neuroticism congruence and a punitive parenting style. A total of 882 Chinese adolescents and their mothers participated in this study. Overall, our results showed that maternal-adolescent high-neuroticism congruence was associated with a more punitive parenting style than low-neuroticism congruence. The more incongruent the maternal-adolescent neuroticism is, the less punitive the parenting style. Moderating effects of adolescent gender on maternal-adolescent neuroticism congruence/incongruence and punitive parenting style. These findings provide a new perspective for exploring the relationship between parent‒child interaction and parenting styles.